Wilms Tumor in Sub-Saharan Africa: Molecular and Social Determinants of a Global Pediatric Health Disparity - Apple, Annie; Lovvorn, Harold N. (Frontiers in Oncology, 2020)
Wilms tumor (WT) is the most common renal malignancy of childhood. Global disparities in WT have been reported with the highest incidence and lowest overall survival occurring in sub-Saharan African nations. After a detailed search of PubMed, we reviewed available literature on WT in sub-Saharan Africa and summarized findings that explore biologic and social factors contributing to this alarming cancer health disparity. Access to care and treatment abandonment are the most frequently reported factors associated with decreased outcomes. Implementation of multidisciplinary teams, collaborative networks, and financial support have improved overall survival in some nations. However, treatment abandonment remains a challenge. In high-income countries globally, WT therapy now is risk-stratified according to biology and histology. To a significantly lesser extent, biologic features have been studied only recently in sub-Saharan African WT, yet unique molecular and genetic signatures, including congenital anomaly-associated syndromes and biomarkers associated with treatment-resistance and poor prognosis have been identified. Together, challenges with access to and delivery of health care in addition to adverse biologic features likely contribute to increased burden of disease in sub-Saharan African children having WT. Publications on biologic features of WT that inform treatment stratification and personalized therapy in resource-limited regions of sub-Saharan Africa have lagged in comparison to publications that discuss social determinants of health. Further efforts to understand both WT biology and social factors relevant to appropriate treatment delivery should be prioritized in order to reduce health disparities for children residing in resource-limited areas of sub-Saharan Africa battling this lethal childhood cancer.